2019
DOI: 10.1007/s12033-019-00191-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of 1-Aminocyclopropane Carboxylic Acid (ACC) Oxidase: Cysteine Mutational Analysis, Characterization, and Bioconjugation with a Nitroxide Spin Label

Abstract: 1-AminoCyclopropane Carboxylic acid Oxidase (ACCO) catalyzes the last step of ethylene biosynthesis in plants. Although some sets of structures have been described, there are remaining questions on the active conformation of ACCO and in particular, on the conformation and potential flexibility of the C-terminal part of the enzyme. Several techniques based on the introduction of a probe through chemical modification of amino acid residues have been developed for determining the conformation and dynamics of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 46 publications
(73 reference statements)
0
21
0
Order By: Relevance
“…ACCO from tomato contains four cysteines in the main core: C28, C60, C133 and C165. In a previous study, we showed that only two of the existing native cysteines are accessible to the P label: C60 and C165 . We then performed a complete mutagenesis study to provide proteins displaying unique modification sites in the main core while retaining their primary structure and function.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…ACCO from tomato contains four cysteines in the main core: C28, C60, C133 and C165. In a previous study, we showed that only two of the existing native cysteines are accessible to the P label: C60 and C165 . We then performed a complete mutagenesis study to provide proteins displaying unique modification sites in the main core while retaining their primary structure and function.…”
Section: Resultsmentioning
confidence: 99%
“…We first generated the double mutants C165H/L292C and C165H/M307C. The enzymes were expressed and purified according to previously reported procedures . Labeling experiments were conducted with the P spin label (Figure C) and the labeled enzymes were analyzed by mass spectrometry (MS) to confirm the introduction of the two labels at the desired positions, namely C60*C292* and C60*C307* (see Table S2 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations